Christ Jesus and the Jewish people today: new explorations of theological interrelationships - Cunningham, Philip A. (William B. Eerdmans, 2011)
"Your privilege: you have Jewish friends": Michael Signer's hermeneutics of friendship / Hanspeter Heinz -- Historical memory and Christian-Jewish relations / John T. Pawlikowski -- Facing history: The Church and its teaching on the death of Jesus / Mary C. Boys -- Jewish comments on Pawlikowski and Boys / Marc Saperstein -- Reading the Epistle to the Hebrews without presupposing supersessionism / Jesper Svartvik -- The gradual emergence of the Church and the parting of the ways / Daniel Harrington -- Jewish comments on Svartvik and Harrington / Tamara Cohn Eskenazi -- The Son of God became a human being as a Jew: on taking the Jewishness of Jesus seriously for Christology / Hans Hermann Henrix -- The dogmatic significance of Christ being Jewish / Barbara Meyer -- Jewish comments on Henrix and Meyer / Edward Kessler -- The tri-unity of God and the fractures of human history / Elizabeth Groppe -- The triune One, the incarnate Logos, and Israel's covenantal life / Philip A. Cunningham and Didier Pollefeyt -- A realm of differences: the meaning of Jewish monotheism for Christology and trinitarian theology / Gregor Maria Hoff -- Jewish comments on Groppe, Cunningham and Pollefeyt, and Hoff / Adam Gregerman -- "The old unrevoked covenant" and "salvation for all nations in Christ": Catholic doctrines in contradiction? / Christian Rutishauser -- The Jewish people at Vatican II: the drama of a development in ecclesiology and its subsequent reception in Ireland and Britain / Thomas Norris -- The affirmation of Jewish covenantal vitality and the Church's liturgical life / Liam Tracey -- Jewish comments on Rutishauser, Norris, and Tracey / Ruth Langer